A case report of anti-GAD65 antibody-positive autoimmune encephalitis in children associated with autoimmune polyendocrine syndrome type-II and literature review - Sapana, Tamang; Li, Wei; Tian, Fengyan; Yan, Wenhao; Dou, Binghua; Hua, Shuang; Zhuo, Zhihong (Frontiers in Immunology, 2023)
Background Glutamic acid decarboxylase (GAD) is the rate-limiting enzyme for the synthesis of gamma-aminobutyric acid (GABA), the major inhibitory neurotransmitter in the central nervous system. Antibodies against glutamic acid decarboxylase (GAD) are associated with various neurologic conditions described in patients, including stiff person syndrome, cerebellar ataxia, refractory epilepsy, and limbic and extra limbic encephalitis. While there are few case reports and research on anti-GAD65 antibody-associated encephalitis in adults, such cases are extremely rare in pediatric cases. Methods For the first time, we report a case of anti-GAD65-positive autoimmune encephalitis associated with autoimmune polyendocrine syndrome (APS) type II. We reviewed previously published pediatric cases of anti-GAD65 autoimmune encephalitis to discuss their clinical features, laboratory tests, imaging findings, EEG patterns, and prognosis. Case presentation An 8-year-old, male child presented to the outpatient department after experiencing generalized convulsions for twenty days. The child was admitted for epilepsy and had received oral sodium valproate (500 mg/day) in another center, where investigations such as USG abdomen and MRI brain revealed no abnormalities, however, had abnormal EEG with diffuse mixed activity in the left anterior middle prefrontal temporal region. On the follow-up day, a repeat blood test showed a very low serum drug concentration of sodium valproate hence the dose was increased to 750 mg/day. Then, the child experienced adverse effects including increased sleep, thirst, and poor appetite, prompting the parents to discontinue the medication. A repeat MRI showed increased signals on FLAIR sequences in the right hippocampus hence admitted for further management. The child's past history included a diagnosis of hypothyroidism at the age of 4, and receiving levothyroxine 75 mcg once daily. His parents are healthy with no history of any similar neurological, autoimmune, or genetic diseases, but his uncle had a history of epilepsy. At presentation, he had uncontrolled blood glucose levels with elevated HbA1c levels. Additionally, the serum and CSF autoantibodies were positive against the anti-GAD65 antibody with the titer of 1:100 and 1:32 respectively. The patient was managed with a mixed type of insulin regimen and received first-line immunotherapy (intravenous immunoglobulin, IVIG) for five consecutive days, followed by oral prednisone and sodium valproate as an antiepileptic drug. Upon achieving a favorable clinical outcome, the patient was discharged with oral medications. Results Among the 15 pediatric patients reported in this literature, nine presented with limbic encephalitis (LE), three with extralimbic encephalitis (ELE), and three with a combination of limbic and extralimbic encephalitis. Most of these cases exhibited T2-W FLAIR hyperintensities primarily localized to the temporal lobes in the early phase, progressing to hippocampal sclerosis/atrophy in the later phase on MRI. EEG commonly showed slow or spike waves on frontotemporal lobes with epileptic discharges. Prognostic factors varied among patients, with some experiencing persistent refractory seizures, type-1 diabetes mellitus (T1DM), persistent memory impairment, persistent disability requiring full assistance, and, in severe cases, death. Conclusion Our findings suggest that anti-GAD65 antibody-positive autoimmune encephalitis patients may concurrently present with other APS. Our unique case presented with multiple endocrine syndromes and represents the first reported occurrence in children. Early diagnosis and timely initiation of immunotherapy are crucial for improving clinical symptoms and reducing the likelihood of relapses or permanent disabilities. Therefore, emphasis should be placed on prompt diagnosis and appropriate treatment implementation to achieve better patient outcomes.